2000
DOI: 10.1034/j.1600-0706.2000.890203.x
|View full text |Cite
|
Sign up to set email alerts
|

Charcoal as a habitat for microbes and its effect on the microbial community of the underlying humus

Abstract: Pietikäinen, J., Kiikkilä, O. and Fritze, H. 2000. Charcoal as a habitat for microbes and its effect on the microbial community of the underlying humus. -Oikos 89: 231-242.Wildfires produce a charcoal layer, which has an adsorbing capacity resembling activated carbon. After the fire a new litter layer starts to accumulate on top of the charcoal layer, which liberates water-soluble compounds that percolate through the charcoal and the unburned humus layer. We first hypothesized that since charcoal has the capac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
367
6
10

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 656 publications
(397 citation statements)
references
References 39 publications
14
367
6
10
Order By: Relevance
“…This was evidently because the complexity of the substrate directly correlates with the number of enzymes required for its degradation. Therefore, the utilization of the complex BC substrate required more N. Similar to our observations, the substrate use pattern of microorganisms changed after BC addition in a forest organic soil horizon (Pietikäinen et al, 2000), and these changes were attributed to the microbial community structure and enzyme activities. The latter is supported by our results because the altered substrate utilization pattern after BC amendment was mainly due to changes in the soil peptidase activity (LAP).…”
Section: Effects Of Biochar and Fertilizer Addition On Soil Enzymes Asupporting
confidence: 86%
See 3 more Smart Citations
“…This was evidently because the complexity of the substrate directly correlates with the number of enzymes required for its degradation. Therefore, the utilization of the complex BC substrate required more N. Similar to our observations, the substrate use pattern of microorganisms changed after BC addition in a forest organic soil horizon (Pietikäinen et al, 2000), and these changes were attributed to the microbial community structure and enzyme activities. The latter is supported by our results because the altered substrate utilization pattern after BC amendment was mainly due to changes in the soil peptidase activity (LAP).…”
Section: Effects Of Biochar and Fertilizer Addition On Soil Enzymes Asupporting
confidence: 86%
“…3A, and Table 1). Previous studies reported an increase in bacterial abundance and altered microbial communities after BC addition under controlled laboratory conditions, which was attributed to the physic-chemical properties of BC (e.g., sorption, pH, chemical properties, habitats) (Anderson et al, 2011;Hale et al, 2015;Pietikäinen et al, 2000). However, such short-term positive effects of the physico-chemical properties of BC on microorganisms under controlled laboratory conditions were not as notable in our long-term field study.…”
Section: Effects Of Biochar and Fertilizer Addition On Microbial Commcontrasting
confidence: 74%
See 2 more Smart Citations
“…However, low-intense pre-monsoon showers likely help selected macrofungal growth, sequester nutrients and restore soil qualities. As porous charcoal adsorb water similar to soil strata (Pietikainen et al 2000), those fungi hidden within partially charred woody litter will be benefitted. During postfire conditions, significant decrease in mycorrhizal species was seen in Cistus and Pinus plots of Spain (Martín-Pinto et al 2006), corroborating with the present study.…”
Section: Discussionmentioning
confidence: 99%